2018
DOI: 10.1016/j.biopsych.2018.04.016
|View full text |Cite|
|
Sign up to set email alerts
|

A Model of Δ9-Tetrahydrocannabinol Self-administration and Reinstatement That Alters Synaptic Plasticity in Nucleus Accumbens

Abstract: We report enduring consequences of THC+CBD use on critical relapse circuitry and synaptic physiology in NAcore following rat self-administration and provide the first report of cue- and stress-induced reinstatement with this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 68 publications
8
75
0
Order By: Relevance
“…Nosepoke discrimination was calculated based on a formula used in [12]: nosepoke discrimination index = (active nosepokesinactive nosepokes)/(active nosepokes + inactive nosepokes), where 0 indicated no discrimination between active and inactive operanda, 1 indicated complete preference for the active operandum, and -1 indicated complete preference for inactive operandum [12]. Effects of AM251 were analyzed using separate repeated-measures one-way ANOVAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nosepoke discrimination was calculated based on a formula used in [12]: nosepoke discrimination index = (active nosepokesinactive nosepokes)/(active nosepokes + inactive nosepokes), where 0 indicated no discrimination between active and inactive operanda, 1 indicated complete preference for the active operandum, and -1 indicated complete preference for inactive operandum [12]. Effects of AM251 were analyzed using separate repeated-measures one-way ANOVAs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CBD facilitates intravenous THC self-administration in rodents [12] (but see [43]) and offsets some of the pharmacological and behavioral effects of THC in humans [44] and rodents [9]. Furthermore, a passive THC+CBD vapor preexposure regimen facilitates the acquisition of intravenous THC+CBD self-administration, possibly by offsetting the novelty of THC intoxication or aversive stimulus properties prior to operant training [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data have demonstrated that cannabinoids, experimenter-or self-administered, abolish LTD in the NAc (Mato et al, 2004(Mato et al, , 2005Neuhofer and Kalivas, 2018;Spencer et al, 2018). Thus, we sought to determine if perinatal WIN exposure elicited similar deficits in LTD in the NAc at adulthood.…”
Section: Perinatal Exposure To Win Alters Synaptic Plasticity and Celmentioning
confidence: 97%